Uma Cartografia para o Intérprete Contemporâneo: Um Lugar entre a Formação e a Criação Coreográfica - Cid Neto, Ângelo (2021)
n the context of contemporary choreography, the dancer emerges as a central figure, not only to think about thematerialization of the choreographic work, but also to shape the creative process. Increasingly, it is required the activeparticipation of the dancer, with his uniqueness, in the thinking of the choreographic work. This perspective allows us toreflect on the student’s training in his teaching-learning process in the context of artistic education in dance. In this way,experimentation, singularity, and heterogeneity are basic concepts to think about the paradigm in the contemporarydancer’s education. This article intends to reflect, based on the characteristics of the dancer, through the dialogue ofthe literature review with the perspectives of some Portuguese choreographers, to project this into an educationaldimension.